Influence of advertising as a means of information transmission towards consumer: theoretical aspect - Vveinhardt, Jolita; Janulienė, Inga (Business: Theory and Practice, 2006)
The article analyses the term of “advertising” with the focus on Information transmission function and a possibil- ity to influence consumers. A comparative analysis of advertising terms is completed. The article presents a different view towards areas of advertising functions and presents aspects of advertising influence on consumers. These aspects form a formula of CAFE’A – cognition, action, finances, emotions and advantage (Lith. PEFEN). There cognition is understood as feelings and recollections of a consumer. Action means that a consumer has noticed and read the ad. Financial aspect of the formula is connected to the costs consumer experiences. Emotional component of advertising impact includes evaluations how consumers accept and value the chosen product. Finally, advantage means the relations among such factors as financial costs, emotions for the bought product and experienced use of a product.